Sustained Release Drug Delivery Systems: A Comprehensive Review - Deepak Chouhan,; Meenakshi Bharkatiya, (Asian Journal of Pharmaceutical Research and Development, 2025)
Sustained release (SR) drug delivery systems have gained significant attention in modern pharmaceutics due to their ability to maintain therapeutic drug levels over extended periods, reduce dosing frequency, and enhance patient compliance. Unlike conventional dosage forms, which often result in fluctuating plasma concentrations and require frequent administration, SR systems are engineered to deliver drugs at a controlled rate, targeted time, and specific site within the body. These systems utilize various formulation strategies, including matrix tablets, reservoir systems, and osmotic devices, often employing hydrophilic or hydrophobic polymers to modulate drug release. Matrix tablets, in particular, represent a versatile and widely used SR approach, providing ease of manufacturing, reproducibility, and cost-effectiveness. Factors influencing the design of SR formulations include drug solubility, polymer type, tablet geometry, and physiological conditions, all of which impact release kinetics and bioavailability. Despite their numerous advantages, challenges such as dose dumping, complex formulation requirements, and stability considerations remain. This review comprehensively explores the principles, classifications, and design considerations of SR drug delivery systems, with a special focus on matrix tablets. Furthermore, examples of marketed SR formulations are discussed to illustrate current industrial applications and trends, highlighting the relevance of these systems in enhancing therapeutic outcomes and patient adherence.